The Influencing Factors of Art Graduates’ Entrepreneurship by Logistic Regression Analysis From the Perspective of Entrepreneurial Mentality - Li, Yanmin; Wang, Xin; Long, Huizhen; Ye, Lele; Gao, Yifang (Frontiers in Psychology, 2022)
The purpose is to understand the influence mechanism of college students' entrepreneurial intention in view of the increasing number of college students at present to alleviate college students' employment competition. The psychological factors that influence the entrepreneurial tendency of art graduates are analyzed and studied. Firstly, venture capital and factors affecting entrepreneurial performance are analyzed. Secondly, the coefficient calculation is carried out for college students majoring in art through the regression analysis of the Logistic model. Finally, a team entrepreneurial performance questionnaire is designed, and team reward levels are discussed. The results show that the Logistic model can well reflect the real situation of the respondents. The significance level sig of the entrepreneurial team is 0.02, which is correlated. Additionally, corresponding suggestions are put forward according to the questionnaire results. Clear team goals, assignment of tasks to members, good pressure resistance and psychological quality of members are necessary qualities for successful entrepreneurship. This conclusion provides a certain theoretical basis for the current college students' entrepreneurial learning and a reliable inspiration for helping college students to successfully start a business.